Respuesta :

════════ ∘◦❁◦∘ ════════

Final value : x² -9x - 11

════════════════════

Step by step

[tex] \frac{1}{(x - 2)} + \frac{1}{(x + 3)} = \frac{1}{5} [/tex]

[tex] \frac{(x + 3) + (x - 2)}{(x - 2)(x + 3)} = \frac{1}{5} [/tex]

[tex] \frac{2x + 1}{ {x}^{2} + 3x - 2x - 6 } = \frac{1}{5} [/tex]

[tex] \frac{2x + 1}{ {x}^{2} + x - 6} = \frac{1}{5} [/tex]

2x + 1 = ⅕ × (x² + x - 6)

2x + 1 = ⅕x² + ⅕x - 6/5

1/5x² +1/5x - 2x - 6/5 - 1 = 0

1/5x² -9/5x - 11/5 = 0

x² - 9x - 11 = 0. #times by 5

════════════════════

#Give me brainliest pls im tired typing all of this